Copper redox mediators with alkoxy groups suppressing recombination for dye-sensitized solar cells. (1st February 2021) - Yang, Kaiyuan; Yang, Xichuan; Zhang, Li; An, Jincheng; Wang, Haoxin; Deng, Zijian
Highlights: The devices obtained a Voc above 1.0 V and a PCE above 10%. The redox potential of 0.65 V makes more dye available. Alkoxy chains increase the solubility of the copper complexes in acetonitrile. Alkoxy group suppress electron recombination with the divalent copper ions. Abstract: Two copper complexes ([Cu(moby)2 ] 2+/+ (moby=6, 6′-bis(methoxymethyl)-2, 2′-bipyridine) and [Cu(eoby)2 ] 2+/+, (eoby=6, 6′-bis(ethoxymethyl)-2, 2′-bipyridine)) with bipyridine ligands were synthesized and used as redox mediators in dye-sensitized solar cells (DSSCs). The DSSCs exhibited high power conversion efficiencies of over 10% under simulated one sun irradiation (100 mW cm −2, AM 1.5G). The introduction of alkoxy groups onto the ligands effectively suppress charge recombination and increased the solubility of the copper complexes in acetonitrile, which led to the high photocurrent and stability of the DSSCs. The redox potentials of [Cu(moby)2 ] 2+/+ and [Cu(eoby)2 ] 2+/+ were 0.65 and 0.70 V, respectively, whereas the open-circuit voltages of their DSSCs were still above 1.0 V. The relatively low redox potentials of the copper complexes enable them to match with more sensitizers to realize DSSCs with high photocurrent and photovoltage, providing an opportunity to further improve DSSCs by optimizing the copper redox mediator. Graphical abstract: Image, graphical abstract